The Theory of Public Administration in Modern Period - Mahmadkhan , Karakhonzoda Muhammednadir (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2022)
This article focuses on a significant aspect of public administration law and the state in contemporary times. The traditional theories of the state and law are considered inadequate in terms of comprehending and analyzing the current scenario. The understanding and analysis of law and the state are crucial for the functioning and stability of society. The article highlights that any theory regarding law and the state is a direct reflection of the societal environment and the outcome of socio-political experiences. It is essential to examine law and state events from the perspective of human values rather than any particular ideology or political party. The article emphasizes the need for a broader perspective and a more comprehensive understanding of law and the state to ensure their effectiveness and efficiency in contemporary times.